Synthesis of a Cr2AlC-Ti2AlC ternary carbide - Kim, Chang-Sam; Hwang, Sung Ik; Ha, Jung-Soo; Kang, Seung-Min; Cheong, Deock-Soo (KOREAN ASSOC CRYSTAL GROWTH, INC, 2010)
The Cr2AlC ternary carbide is excellent in chemical and oxidation resistances as well as mechanical properties at high temperatures. Therefore it satisfies most requirements for as an interconnector Material in solid oxide fuel cells (SOFCs). However, its thermal expansion coefficient is higher than those of the anode and cathode so that a high thermal stress is generated unavoidably between them during heating and cooling SOFCs. Thus we attempted to reduce the thermal expansion coefficient through a solid solution with Ti2AlC which has a lower thermal expansion coefficient. Dense and single phase (Cr1-xTix)(2)AlC solid solutions with a relative density of 99.5% or more were synthesized by hot pressing a mixture of CrCx, Ti2C, Al powders at 1250 degrees C for 4 h. The limitation of Ti substitution was found to be less than 20 mol%. When Ti substitution exceeded this limit, unreacted Ti2C, Cr7C3, and Cr3C2 remained as second phases. The grain size decreased with Ti substitution. With 5 mol% Ti substitution, the thermal expansion coefficient could be lowered by 5% compared with the case without substitution in the temperature range of 700-800 degrees C.
Keywords: MECHANICAL-PROPERTIES; OXIDATION; CR2ALC; 1300-DEGREES-C; TI3SIC2